ANALISIS DAERAH PENANGKAPAN UDANG PENAEID BERDASARKAN FAKTOR FISIKA, KIMIA DAN BIOLOGI DI PERAIRAN PANTAI PAYUM LAMPU SATU KABUPATEN MERAUKE PAPUA - Lantang, Bonny; Merly, Sendy Lely (AGRICOLA, 2017)
The aims of these research were to 1). Analyzed the influence of oceanographic factors such as physics, chemistry and biology of the existence of penaeid shrimp in the Payum coastal waters until Lampu Satu. 2). Determined fishing ground of penaeid shrimp at The Coastal Waters Payum-Lampu Satu; which the basis for shrimp fishing coastal communities. The data were took directly through measuring the oceanography parameters such as temperature, tidal range, water transparency, salinity, pH and abundance of phytoplankton. While the data obtained by weighing the catch of penaeid shrimp catches in every trip. To analized the data regression models were used to determine the influence of oceanographic factors on catches. The results showed that the temperature and water transparency affected the Penaeid shrimp catch while the potential fishing areas in the region of the coordinates 80 33’ 17.61“ S – 80 34.’ 2“ S dan 1400 25’ .95’ E– 1400 25’ 44”E . The total catches around 50 to 69.9 kg.